Social Economic Resilience in Facing Land and Forest Fire Disaster (Case Study in South Sumatra Province) - Deffi Ayu Puspito Sari; Freddy Rumambi; Ratih Nurmasari (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
Forest and land fires in South Sumatra Province tend to be a routine disaster in the dry season. The handling of forest and land fires needs to be linked to socio-economic resilience in order to be completely resolved. This study measures socio-economic resilience and links it with forest and land fires. The method used is qualitative analysis using the resilience concept of UNISDR. The result shows that all socio-economic resilience indicators in facing the disaster have been done by South Sumatera Provincial Government but not yet maximal. Some indicators that need to be improved are the diversification of local economic activities, the implementation of contingency plans in the event of a disaster, the establishment of incentives and clear penalties, and the increase of multi-stakeholder participation.